Challenges on Construction Projects at SUKE Highway Alam Damai Interchange - Mohd Fadhillah, Muhamad Haziq; Omar, Roshartini; Masrom, Md Asrul Nasid; Seow, Seow Ta Wee (Research in Management of Technology and Business, 2024)
The construction industry is one of the industries that plays a vital function in the development and enhancement of the economy as well as the development of a country. Highway projects are typically classified as high-risk projects because of how crucial they are to the socioeconomic, political, and economic growth of a nation. Therefore, this research is to identify the challenges that exist during the construction of SUKE Highway Alam Damai Interchange, identifying the impact of the challenges towards the process to completing the project, and investigating methods to control the challenges from disturbing the completion of construction process. This research focused on G7 grade contractors’ company and there have 4 respondents been interviewed which are planning engineer, safety health officers, traffic management officer, and site engineer. This research was conducted using qualitative methodology by interview session. The results of the study found that the challenges on the construction process of SUKE Highway have given major impact to the progress of the project. While impact of the challenges such as contributed to accident occur, delay, cost overrun, high cost of poor quality and poor quality of the construction have occurred. Next, the strategy to control the challenges such as safety check and safety signs, implementing the latest management tools, absorbing, and training of more skilled workforce and technology use to improve communication have help to mitigate the challenges. In conclusion, this study can help the government and industry leaders get realistic ideas to improve the quality of the construction highway in Malaysia for future.